Intravenous amodiaquine and oral amodiaquine/erythromycin in the treatment of chloroquine-resistant falciparum malaria. - Looareesuwan, S; Phillips, R; White, N; Karbwang, J; Benjasurat, Y; Attanath, P; Warrell, D (1985)
In eastern Thailand, 14 adults with moderately severe falciparum malaria were treated with intravenous amodiaquine dihydrochloride, loading dose 10 mg base/kg infused over 4 h followed by three further intravenous infusions of 5 mg base/kg at 24, 48, and 72 h. All patients were clinically cured--mean fever clearance time 37.8 h (range 24-60), mean parasite clearance time 64.9 h (18-164). There were no serious toxic effects. 33 patients aged over 5 years with uncomplicated falciparum malaria were given oral amodiaquine dihydrochloride (mean total dose 41 mg base/kg over 3 days) combined with erythromycin estolate (mean dose 48 mg base/kg daily for 5 days). 2 patients failed to respond. In the other 31 patients mean fever clearance time was 55.9 h (range 10-104) and mean parasite clearance time was 65.4 h (40-120). In both studies, more than half the patients followed-up had recurrent parasitaemia but reinfection could not be excluded. Parasites isolated from 18 patients were highly resistant to chloroquine in vitro.